Total synthesis of (±)-(1β, 4β, 4aβ, 8aα)-4, 8a-dimethyl-octahydro-naphthalene-1, 4a(2H)-diol. Issue 10 (11th April 2018) - Liu, Qingyin; Han, Li; Qin, Bing; Mu, Yu; Guan, Peipei; Wang, Songyao; Huang, Xueshi
Abstract : The first total synthesis of (±)-(1β, 4β, 4aβ, 8aα)-4, 8a-dimethylocta-hydronaphthalene-1, 4a(2 H )-diol (1 ), a degraded sesquiterpene isolated from a fermentation broth of Streptomyces albolongus, has been achieved via three different synthetic approaches (13–15 steps) starting from racemic Wieland–Miescher ketone (2 ). Abstract : The first total synthesis of (±)-(1β, 4β, 4aβ, 8aα)-4, 8a-dimethylocta-hydronaphthalene-1, 4a(2 H )-diol (1 ), a degraded sesquiterpene isolated from a fermentation broth of Streptomyces albolongus, has been achieved via three different synthetic approaches (13–15 steps) starting from racemic Wieland–Miescher ketone (2 ). The configuration of hydroxyl groups at C-1 and C-4a in1 was availably managed using the Mitsunobu reaction and stereo- and regioselective epoxidation. Moreover, the syntheses of configuration isomers12, 17, 45 and54 were also described in the present study.